1999
DOI: 10.1292/jvms.61.991
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Major Piroplasm Surface Protein Genes and Their Allelic Variants of Theileria Parasites in Thai Cattle.

Abstract: ABSTRACT. Twenty-eight field isolated Theileria parasite DNAs obtained from dairy and beef cattle in distinct geographical areas of Thailand were characterized by using polymerase chain reaction (PCR) amplification with six sets of oligonucleotide primers. Three sets of them were modified from two genes of immunodominant major piroplasm surface protein (MPSP) coding for 32 kDa (p32) of T. sergenti and 33/34 kDa (p33/34) of T. buffeli, and MPSP of Theileria spp.(Thai-isolate). The other three sets of primers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The molecular weight of MPSP ranges from 30 to 40 kDa [8,19]. Recently, the nucleotide sequences of MPSP genes were used in epidemiological and phylogenetic research [4,5,9,12,13,17]. The populations of benign Theileria parasites differentiated by using allelic MPSP gene types are listed in Table 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular weight of MPSP ranges from 30 to 40 kDa [8,19]. Recently, the nucleotide sequences of MPSP genes were used in epidemiological and phylogenetic research [4,5,9,12,13,17]. The populations of benign Theileria parasites differentiated by using allelic MPSP gene types are listed in Table 1.…”
mentioning
confidence: 99%
“…In Thailand, different species or variants of Theileria parasites were found and designated as Thai-type, C-type and B-type [7,17]. However, the distribution of benign Theileria parasites in this country has not been fully studied.…”
mentioning
confidence: 99%
“…For further analysis of parasite populations, field isolates were collected from Asian countries (Korea, China, Taiwan and Thailand) and others (Australia and Italy). This analysis showed that the I type parasites were commonly found in Korean isolates [3,7,8,10] but not in Taiwan [18], Thailand [14,15], Australia [9] and Italy [16]. In the present study, we characterized field-collected isolates of Theileria in cattle from Cambodia and Vietnam using allele-specific PCR in order to obtain further epidemiological information of T. orientalis in Southeast Asia.…”
mentioning
confidence: 92%
“…In Korea, all Theileria isolates contained the I type pathogenic than the C and the B type parasites and infected cattle manifest severe clinical symptoms [3,8], whereas the non-pathogenic C type is documented in Taiwan [18] and Italy [16]. In Thailand, where the Thai and C types exist, theileriosis has never been reported [15]. On the basis of these epidemiological studies, C type parasite is considered to be an universal and apathogenic type.…”
mentioning
confidence: 99%
“…2 Recent studies using the major piroplasm surface protein (MPSP) and small subunit ribosomal RNA (ssrRNA) gene indicated that Thai isolates of Theileria are more closely related to the T. sergenti/buffeli/orientalis group parasites than to malignant species of Theileria. [2][3][4] Since the pathogenesis of the benign Theileria species is found to be related to the proliferation of the parasites in the host's red blood cells, chemotherapy of the benign theileriosis has mainly been focused on destroying the intraerythrocytic stages. Although some drugs are currently available for the treatment of bovine theileriosis, they are not necessarily satisfactory because of their adverse effects and the emergence of parasite with increased drug resistance.…”
Section: Introductionmentioning
confidence: 99%